Pediatric pituitary neuroendocrine tumors–a 13-year experience in a tertiary center - Li, Xiaoxu; Deng, Kan; Zhang, Yi; Feng, Ming; Xing, Bing; Lian, Wei; Yao, Yong (Frontiers in Oncology, 2023)
Introduction: Pediatric pituitary neuroendocrine tumor is a rare condition, and despite previous research focusing on this specific group, the main factors influencing the surgical cure rate have not been identified.We conducted a single-center retrospective study on pediatric pituitary neuroendocrine tumour patients who visited Peking Union Medical College Hospital between 2010 and 2023. We collected data on their clinical characteristics, imaging features, surgical outcomes, and follow-up information. Additionally, we used multiple-factor logistic regression to investigate the factors affecting the surgical cure rate of pediatric pituitary neuroendocrine tumour.Results: 232 patients were diagnosed with pediatric pituitary neuroendocrine tumours, with a higher incidence in females. The most common type was ACTHsecreting adenoma (90/232), followed by prolactin-secreting adenoma (64/232), and growth hormone-secreting adenoma (41/232). The majority of pediatric adenomas were macroadenomas (139/232), and some tumors were associated with cystic changes or hemorrhage (58/232), while a few exhibited invasion of the cavernous